Migrant Filipino Workers: Impact on the Values Orientation of College Students with OFW Mothers - Kimberly Ann S. Cantilero; Gerald A. Escleto; Charity F. de Luna; Rainier S. Ladic; Mark Ivhan B. Arceo; Chiqui C. Patio; Armand Vincent A. Sese; Venessa Charm N. Miclat; John Ezequel V. Murillo; Antonio Ponciano L. Rodil (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Maternal labor migration has become a defining feature of Filipino family life, reshaping caregiving arrangements and developmental contexts for children left behind. While economic benefits are well documented, less is known about how prolonged maternal absence influences the values of young people in emerging adulthood. This study examined the values orientation of college students with Overseas Filipino Worker (OFW) mothers within a transnational family context. Guided by Bronfenbrenner’s Ecological Systems Theory and Schwartz’s Theory of Basic Human Values, the study employed a qualitative descriptive design using open-ended written responses collected through an online questionnaire and analyzed using thematic analysis. Eight first-year college students whose mothers had worked overseas since early childhood were purposively selected from a private higher education institution in the Philippines.  Five interrelated themes emerged: material stability amid emotional scarcity, accelerated independence and self-reliance, emotional distance and adaptive relational patterns, school engagement as responsibility rather than attachment, and future orientation shaped by sacrifice and aspiration. The findings indicate that maternal migration reorganizes students’ value systems, heightening the salience of independence, resilience, duty, and achievement while sustaining strong family-oriented commitments. Rather than uniformly impairing development, maternal absence prompts adaptive negotiation between loss and opportunity. The study underscores the need to view children of migrant mothers as active agents who construct moral meaning within altered family ecologies and highlights the importance of supportive interventions for transnational Filipino families.